Protection Consumer In Pre-Order Based Transactions Salam Contract : The Role of Sharia Fintech and Mechanisms - Romzatul Widad; Hanin Fara Atiqoh (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The development of digital technology encourages changes in economic transaction practices, including the use of pre-order systems for UMKM. However, from the perspective of sharia economics, this practice still faces problems such as delays in delivery, mismatches of goods, and lack of transparency that have the potential to cause elements of gharar. Akad salam is a relevant concept in this transaction, while sharia fintech with an escrow mechanism can act as a consumer protection solution. This study aims to analyze the suitability of pre-order practices in Ayubi Hijab Kraksaan UMKM with the salam contract and examine the role of sharia fintech and escrow mechanisms. The method used is a qualitative approach with a case study design through interviews, observations, and documentation. The results of the study show that the practice of pre-ordering has fulfilled some of the principles of the salam contract, especially in advance payment and clarity of goods specifications, although there are still obstacles to the timeliness and suitability of products. The implementation of the escrow mechanism has been proven to increase transaction security, consumer confidence, and minimize the risk of default. Therefore, the integration of salam contracts, sharia fintech, and escrow is an innovative model that supports digital transactions that are transparent, fair, and in accordance with sharia principles.